Volatility, procyclicality and productivity of public spending in Venezuela. Lapse 1986-2010 (Teorías, Enfoques y Aplicaciones en las Ciencias Sociales, 2012)
The work performed here aimed to examine the efficiency of public spending in relation to its quality or productivity factor generating economic growth, taking as a standard measure internal product development for the period studied. Also discusses some salient features of the Venezuelan Government Finance such as the volatility and cyclicality of public spending, characteristics such as movements understood in the sense of public spending variables and Gross Domestic Product. The documentary research is of descriptive nature, to the effects, the verification of the hypothesis is made by reviewing specialized sources in economic and fiscal issues, including statistical series published by lead agencies in the economic and national and international Fiscal, of these sources the information was obtained for analysis of the behavior of the variables under study, as in the case of spending statistics, these correspond entirely to the financial result of the Central Government Budget. The results show a continued decrease in the productivity of current expenditure over the formation of new wealth or real output, plus a high inelasticity is found between public expenditure and domestic product as a clear manifestation of the phenomenon of volatility and procyclicality.
Keywords: public spending; gross domestic product; volatility; procyclicality